USING ICE BREAKING ACTIVITIES TO SUPPORT CLASSROOM MANAGEMENT IN EFL CLASSROOMS - Avrilia Cantika Rani; Nailul Husna; Andini Putri; Nurma Indah Daulay; Rahma Oktavia; Cut Raudhatul Miski (UIN Sumatera Utara, 2026)
Classroom management plays a crucial role in determining the success of English as a Foreign Language (EFL) learning. However, EFL classrooms often face challenges such as students’ low confidence, limited participation, and learning boredom, which may reduce engagement and learning effectiveness. This study aims to analyze the role of ice breaking activities in supporting classroom management, identify effective types of ice breaking activities, and examine their benefits in improving students’ attention, participation, and classroom atmosphere. This study employed a qualitative approach using a literature review design. Data were collected from relevant academic journals, books, and scholarly articles, and analyzed using descriptive qualitative techniques. The findings reveal that various types of ice breaking activities, including word games, guessing games, short conversational activities, and movement-based activities, can effectively enhance student engagement. The implementation of ice breaking activities at different stages of the lesson helps maintain students’ focus, reduce boredom, and create a positive learning environment. Furthermore, ice breaking activities contribute to improving students’ confidence, participation, and social interaction. Ice breaking activities are not merely supplementary tools but essential strategies that support effective classroom management in EFL settings. Their proper use can significantly improve the overall quality of the teaching and learning process.